Innovation and development of fitness facility management evaluation instrument: validity and reliability - Inas Gita Amalia; Suharjana Suharjana; Ahmad Nasrulloh; Danny Eka Wahyu Saputra; Muhammad Fatih Humam; Dewi Kiani Cakrawati (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Objective: This study aimed to develop a questionnaire as an instrument to evaluate management practices in fitness facilities.